Linking Leadership Style to Employee Performance with Job Satisfaction as a Mediation - Ratna Mitasari; Achmad Sani Supriyanto; Vivin Maharani Ekowati (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
The problem of this research is whether the Leadership Style affects employee performance through job satisfaction. This study aims to explain the effect of leader-member exchange (LMX) on employee performance by mediating job satisfaction. This study uses one type of explanation to examine the effect of LMX on employee performance and mediates job satisfaction. The sampling technique used in this study was saturated sampling, where the total population studied was 108 respondents. This research tool is a questionnaire, after which the information obtained is processed with path analysis. The results of this study indicate that LMX has a significant effect on employee performance, and job satisfaction has a significant effect on employee performance. The results of this study also indicate that job satisfaction can mediate the effect of LMX on employee performance